Optimal structure of reactive and non-reactive stages in reactive distillation processes - Domancich, Alejandro Omar (2007)
We present a model for a reactive column, based on models by Taylor and Krishna (2000) and Almeida-Rivera (2005), shown in detail in Domancich et al (2006). It consists in pure separation stages combined with a reactive distillation sector, where both reaction and separation take place at the same time. For this study, we used a rigorous modeling of the column, with an equilibrium model for the reactive sector. An example showing the performance of a reactive distillation unit used for the production of MTBE is presented. The economic optimization of the reactive distillation process is performed using a MINLP algorithm and the cost of the resulting scheme is compared to the cost of the conventional process considering that reaction and separation take place in different equipment.